Critical heat flux enhancement in narrow gaps via different-mode-interacting boiling with nonuniform thermal conductance inside heat transfer plate. (April 2019) - Utaka, Yoshio; Xie, Tianxi; Chen, Zhihao; Morokuma, Takayuki; Ohkubo, Hidetoshi
Highlights: CHF enhanced by interaction of different boiling modes in narrow gap boiling. Different modes were achieved by surface temp. distribution using PTFE inside plate. CHF for nonuniform plate was significantly enhanced compared with uniform plate. Maximum CHF enhancement ratio was 68% for 1.0 mm material width and 0.5 mm gap. Abstract: To improve the critical heat flux (CHF) of boiling heat transfer in open narrow gaps in a water pool, a method of different-mode-interacting boiling, in which the interactions between the different modes of nucleate and film boiling were expected, was investigated. Two types of thin materials with different thermal properties were alternately arranged inside the heat transfer plate near the surface (nonuniform conductance) was applied to realize the nonuniform temperature distribution on the heat transfer surface. Experiments with three different widths of two materials, namely PTFE and copper and three gap sizes for a 20 mm 2 heat transfer surface were performed. It was shown that the CHF in the narrow gaps of the heat transfer plate with nonuniform conductance significantly increased compared with the uniform heat transfer plate made of copper. The ratios of CHF enhancement were 34–43%, 47–68%, and 26–32% for width of nonuniform materials of 0.5, 1.0, and 2.0 mm, respectively, with gap size of 0.54–2.01 mm.